2003
DOI: 10.1097/00004836-200305000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Gastric Atrophy After Helicobacter pylori Eradication Therapy

Abstract: Gastric atrophy was improved in the corpus approximately 2 years after H. pylori eradication therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 27 publications
2
22
3
Order By: Relevance
“…A possible explanation for atrophy improvement in the corpus but not in the antrum is not at hand. However, it might be attributed to the frequent observation of a more severe antrum versus gastric body atrophy 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation for atrophy improvement in the corpus but not in the antrum is not at hand. However, it might be attributed to the frequent observation of a more severe antrum versus gastric body atrophy 25 …”
Section: Discussionmentioning
confidence: 99%
“…However, it must be noted that 3/25 studies involved a follow‐up period of more than 12 months post‐ H pylori eradication, and only one had a follow‐up of more than 2 years. This latter time‐point might be a critical, and has already been proposed as the cut‐off for documenting changes in gastric atrophy after H pylori eradication 25 …”
Section: Discussionmentioning
confidence: 99%
“…Following eradication of H. pylori, the active gastric mucosal inflammation diminishes rapidly [11] and the risk for PUD is eliminated [12]. However, existing premalignant histological changes may persist [13], and lately it has been shown that this also holds for the risk of developing future malignancy, despite eradication of the infection, if MA and IM can be detected before eradication [14].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies reported on H. pylori eradication and follow-up in the last 5 years were from Japan (6)(7)(8)(9)(10) and the others were single studies from Western countries (11)(12)(13)(14)(15). From these studies, discrepancies among the results were noticed and it was concluded that atrophy and IM were reversible only in some patients regardless of the sample size and the follow-up period.…”
mentioning
confidence: 99%